1983
DOI: 10.1128/iai.39.1.213-219.1983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endotoxin treatment on dexamethasone induction of hepatic phosphoenolpyruvate carboxykinase

Abstract: Decreased glucocorticoid binding has been observed at a time after endotoxin (3 to 6 h) when imparied liver enzyme induction is known to occur. This study was undertaken to characterize the early time course of hypoglycemia and decreased liver phosphoenolpyruvate carboxykinase (PEPCK) activity in intact and adrenalectomized mice given endotoxin. In addition, altered steroid induction of hepatic PEPCK was examined in adrenalectomized mice given dexamethasone at intervals before and after a median lethal dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Further evidence that the endotoxin effects reported here are related to glucocorticoid mechanisms of action was presented by McCal-lum et al (19) who studied hypoglycemia in adrenalectomized mice given endotoxin. An initial hyperglycemia (1 h after treatment), preceding a severe hypoglycemia seen after endotoxin treatment of intact mice, was absent in adrenalectomized mice.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Further evidence that the endotoxin effects reported here are related to glucocorticoid mechanisms of action was presented by McCal-lum et al (19) who studied hypoglycemia in adrenalectomized mice given endotoxin. An initial hyperglycemia (1 h after treatment), preceding a severe hypoglycemia seen after endotoxin treatment of intact mice, was absent in adrenalectomized mice.…”
Section: Discussionsupporting
confidence: 60%
“…Results from previous studies have demonstrat-614 STITH AND McCALLUM ed less specific binding of [3H]dexamethasone in liver cytosol prepared from endotoxin-treated mice than in untreated controls at a time when the animals exhibit hypoglycemia and diminished hepatic phosphoenolpyruvate carboxykinase activity (19,20). This study was undertaken to characterize further the changes in [3H]dexamethasone binding associated with endotoxemia.…”
mentioning
confidence: 99%
“…Berry et al (5) first observed in mice an inhibitory effect of endotoxin on the glucocorticoid induction of the rate-limiting enzyme of gluconeogenesis, phosphoenolpyruvate carboxykinase (PEPCK). We observed subsequently that mice given a 50% (LD50) lethal dose of Salmonella typhimurium endotoxin were hyperglycemic at 1 h after treatment; however, the animals became hypoglycemic at 3 and 6 h (39). Coincident with this pattern, hepatic PEPCK activity decreased as early as 3 h after endotoxin.…”
mentioning
confidence: 81%
“…Liver cytosol preparations were obtained by homogenizing livers in 0.25 mM Tris-sucrose (pH 7.4) containing 5 mM dithiothreitol and centrifuging them at 468,000 x g for 10 min in a TL-100 tabletop ultracentrifuge (Beckman Instruments, Inc., Palo Alto, Calif.). PEPCK enzyme activity was measured by a 14C radiometric method as described previously (39). Units of enzyme activity correspond to nanomoles of oxaloacetate formed from phosphoenolpyruvate per 15 min per milligram of cytosol protein.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies suggest additional potentially relevant targets for beneficial effects of glucocorticoids. These include, for example, increased expression of phosphoenolpyruvate carboxykinase in the liver (13,15) and regulation of arachidonic acid metabolism (22,24). Adrenalectomy and hypophysectomy, which serve to deplete endogenous sources of glucocorticoids, have effects opposite those of glucocorticoids, including increased sensitivity to the lethal effects of endotoxin (3,17,21,26), lowering of hepatic phosphoenolpyruvate carboxykinase (15), and increased serum TNF-ct levels in endotoxin-challenged animals (17,26).…”
Section: Discussionmentioning
confidence: 99%